Water science policy and management : a global challenge - Dadson, Simon J. (John Wiley & Sons, Inc., 2020)
"Understanding the risks and opportunities presented by the changing water cycle, and the intensifing demands and competition for freshwater, are some of the most pressing challenges facing scientists, water managers and policymakers. In the context of rapid climate, land cover and other environmental changes, the requirement to protect communities against water-related natural hazards; the stewardship of water resources to provide reliable water quantity and quality, and the provision of clean, safely-managed drinking water and improved sanitation to a population predicted to exceed 9 billion, constitute a defining challenge for the 21st century. This challenge has inspired the University of Oxford to offer a graduate programme in Water Science Policy and Management since 2004, which to date has seen over 350 students from 55 countries graduate, of which more than half are women. This book is formed from contributions from more than a dozen academics and practitioners who have taught the course, in each case writing in co-authorship with more than two dozen alumni"--